MEL scripting for Maya animators - Wilkins, Mark R. (Morgan Kaufmann series in computer graphics and geometric modeling., 2005)
MEL scripting for Maya animators, 2nd edition, includes new features, such as a discussion of global procedures, new chapters on fixing programming bottlenecks, advanced user interface techniques, and optimizing character rigs. New chapters on utility nodes and Maya's Web Panel feature provide new ideas on how to use MEL in applications--Resource description page.